Sulfate radicals based heterogeneous peroxymonosulfate system catalyzed by CuO-Fe3O4-Biochar nanocomposite for bisphenol A degradation. (June 2021) - Zhen, Jianyuan; Zhang, Shuoshuo; Zhuang, Xuming; Ahmad, Shakeel; Lee, Taeho; Si, Hongyu; Cao, Chengbo; Ni, Shou-Qing
Graphical abstract: Highlights: CuO-Fe3 O4 -BC/PMS system showed high adsorption and catalysis for BPA degradation. The effect of copper and iron ions accelerated the free radical generation. SO4 − was the dominant reactive radical species in CuO-Fe3 O4 -BC/PMS system. CuO-Fe3 O4 -BC nanocomposite processed high stability and reusability. Abstract: Magnetic CuO-Fe3 O4 -Biochar (CuO-Fe3 O4 -BC) nanoparticles were successfully synthesized by two steps of coprecipitation and calcination and were characterized as a heterogeneous catalyst to activate peroxymonosulfate for bisphenol A (BPA) degradation. The reaction process and mechanism of heterogeneous catalyst adsorption and synergistic catalytic oxidation for the removal of BPA in CuO-Fe3 O4 -BC/PMS system were extensively evaluated in view of the practical applications. Results indicated that the addition of CuO achieved a high removal efficiency of BPA in a wide pH range. BPA removal efficiency reached 100 % in 30 min by using 2.0 g/L CuO-Fe3 O4 -BC and 5 mM PMS at a pH of 9.0, and SO4 − played an essential role in the degradation process. The synergistic effect of copper ions and iron ions accelerated the circulation of Fe (II)/Fe (III) and Cu (I)/Cu (II), which improved the electron transfer on the catalyst surface and increased the free radical generation rate. CuO, Fe3 O4 and BC achieved a synergistic effect between adsorption and catalysis. The stability and reusability of CuO-Fe3 O4 -BC/PMS system offer an approach in organic pollutant wastewater treatment since it has great advantages of high removal efficiency, conducting under neutral conditions, energy-saving and avoiding the common issues in traditional Fenton reactions.